Tocotrienol Rich Fraction from Palm Oil Reduces Plasma and Erythrocyte Membrane Lipid Alteration in Diabetic Rats: Tocotrienols Reduce Dyslipidemia in Plasma and Erythrocytes - Nasar Alwahaibi; Siti Balkis Budin; Zariyantey Abdul Hamid; Jamaludin Mohamed; Jalifah Latip; Norzamzurina Binti Ismail; Alefee Bin Ayatillah; Fatmah Ali Matough (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Tocotrienol-rich fraction (TRF) from palm oil has been shown to exhibit potent antioxidative properties in various pathological conditions. This study aimed to determine the antioxidative properties of TRF on the plasma and erythrocyte membrane lipids composition in streptozotocin-induced diabetic rats.METHODS: Male Sprague-Dawley rats (n=40) were divided randomly into four groups of 10, which were a normal group, a normal group with TRF, a diabetic group, and a diabetic group with TRF. Following four weeks of treatment, lipids compositions in the plasma and erythrocyte membrane were investigated.RESULTS: TRF significantly reduced the plasma total cholesterol, to that in the diabetic group. In addition, supplementation of TRF was able to reduce the very low density lipoprotein cholesterol (VLDL-C), triglycerides levels in treated diabetic rat although no significant different was observed when compared with untreated diabetic rats alone. Furthermore, TRF supplementation showed increased the levels of phosphatidylinositol, phosphatidylserine, and total phospholipid levels in diabetic rats. However, the linoleic acid (18:2) levels were reduced in diabetic rats compared to the control group, and the eicosadienoic acid (20:2) levels were significantly increased by TRF supplementation in diabetic rats.CONCLUSION: Supplementation with 200 mg/kg TRF improves dyslipidemia and that TRF, therefore, might have protective effects against oxidative damage of phospholipids. This study also showed the antioxidative properties of TRF on the erythrocyte membrane lipids composition, in particular, its protective effects against peroxidation of unsaturated fatty acids.KEYWORDS: antioxidative property, cholesterol, fatty acids, phospholipids, tocotrienol-rich fraction